Trends in forest Management in India-Case of Sambalpur Division in Odisha - Paul, Shashi (Indian Forester, 2015)
Sambalpur, one of the western most districts of present Odisha state was part of Central Province till 1904. Forest conservancy efforts started in the second half of 19th century and the forest division went through many changes like bifurcation into two divisions in 1928 and again unification in 1959. Again in 2003, it was divided. In 1985, Debrigarh Sanctuary was carved out of the division. Forests mainly fall under the category of dry and moist deciduous forests with bamboo brakes. Forest management through working plans started in the year 1895-96. In the initial years, forests were worked under coppice, selection and conversion to uniform silvicultural systems. Later on, towards the end of 20th century coppice system was discontinued and improvement and rehabilitation systems were given more coverage with very small part under selection system. More or less the forest management has progressed as per broader policy guidelines from time to time, except balancing of production and conservation under 1988 National Forest Policy. By the start of the 21st century, production has gone down drastically though demand has gone up manifold. Obviously, this might have led to more supply from illegal sources. Wildlife management was almost totally missing from working plans of pre-independence period but after independence it has gained its due place in forest management. Other aspects which gained importance over time are afforestation activities and minor forest produce or non-timber forest produce (NTFP).